Implementasi Toleransi Kebhinnekaan Pada Masyarakat Majemuk Di Dusun Cetho Desa Gumeng Kecamatan Jenawi Kabupaten Karanganyar - Wibowo, Aji; , Drs. Yulianto Bambang Setyadi, M.Si (2017)
This research aims to describe the implementation, the constrains and effort in the implementation of tolerance for diversity in a pluralistic society in the hamlet village Cehto Gumeng Jenawi district of Karanganyar. Collecting data in this research with interview, observation, and documentation. Data analysis techniques by apolying interview models through data collection, and drawing conclution. Test the validity of the data in this research by mean of triangulation techniques and resources. This result show that 1). Implementation of tolerance for diversity in society is reflected Cetho hamlet of respect for religious differences; 2). Barriers to Iimplementation tolerance of diversity in a pluralistic society in the hamlet village Cetho Gumeng Jenawi Distric of Karanganyar that his marriage of different religious and a lack of public understanding of the political right; 3). community efforts to overcome obsracles in the implementation of tolerance in pluralistic society in the hamlet village Cetho Gumeng Jenawi Karanganyar Subdistrict hamely deliberation and socialization of politics right way. Keyword: Implementation, tolerance of diversity, pluralistic society.